Analisis Prinsip Demokrasi Dalam Konstitusi Indonesia: Tinjauan Terhadap Implementasi Dan Tantangannya - Maximiliania Krismarmita Brahman; Geal Aditya Christian; Nabila Sanina Fadhilah; Nayya Devi Denita (Lembaga Pengembangan Kinerja Dosen, 2024)
This analysis focuses on the democratic principles contained in the Indonesian Constitution and how they are implemented as well as the challenges faced. The Indonesian Constitution, which is based on popular sovereignty, is considered the basis for the implementation of democracy in Indonesia. However, in practice, the implementation of democracy still faces several challenges, such as political corruption, identity politics, and the spread of false information. This research uses a normative juridical approach to analyze the regulations governing the democratic system and elections in Indonesia, including the 1945 Constitution and the Election Law. The results show that although democracy in Indonesia has been running for several years, there are still many challenges faced, such as a lack of political literacy and public knowledge of democratic principles. In this analysis, the research also discusses the implementation of Pancasila Democracy, which is based on indigenous Indonesian values. Pancasila Democracy is considered the right choice for the Indonesian state, but it still needs to be balanced with good political literacy and knowledge so that freedom of speech is not abused.